Phenological response of a key ecosystem function to biological invasion. (2nd March 2016) - Alp, Maria; Cucherousset, Julien; Buoro, Mathieu; Lecerf, Antoine
Abstract: Although climate warming has been widely demonstrated to induce shifts in the timing of many biological events, the phenological consequences of other prominent global change drivers remain largely unknown. Here, we investigated the effects of biological invasions on the seasonality of leaf litter decomposition, a crucial freshwater ecosystem function. Decomposition rates were quantified in 18 temperate shallow lakes distributed along a gradient of crayfish invasion and a temperature‐based model was constructed to predict yearly patterns of decomposition. We found that, through direct detritus consumption, omnivorous invasive crayfish accelerated decomposition rates up to fivefold in spring, enhancing temperature dependence of the process and shortening the period of major detritus availability in the ecosystem by up to 39 days (95% CI: 15–61). The fact that our estimates are an order of magnitude higher than any previously reported climate‐driven phenological shifts indicates that some powerful drivers of phenological change have been largely overlooked.